Yield and yield components of tomato grafted plants in the high Andean region of Colombia - Ramírez-Jiménez, Jamer Alexis; Barrera-Sánchez, Carlos Felipe; Córdoba-Gaona, Oscar de Jesús (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2020)
Grafting as a technique is gaining attention, and the production and demand for grafted vegetable plants have increased worldwide, especially for greenhouse cultivation. This study aimed to evaluate the potential of different scion × rootstock combinations or improving the yield of the tomato crop under greenhouse conditions. For this purpose, a scion of tomato cv. Libertador was grafted on two commercial tomato rootstock (‘Olimpo’ and ‘Armada’) and cultivated in a greenhouse in a randomized complete block experiment design, with four scion-rootstock combinations: vigor and resistance rootstocks, self-grafting and non-grafted plants. The yield and yield components were evaluated (number and weight of the fruits of extra, commercial, and non-commercial quality, weight per cluster, and weight per fruit).  Although vigor rootstocks produce less fresh fruit in the first harvests, from the seventh harvest onwards, the vigor rootstocks outperformed the other treatments in the accumulated yield by producing 37, 22 and 22% more yield, and 60, 30 and 40% higher number of fruits of extra quality in the resistance rootstock, self-grafted, and non-grafted plants. The fruits plants of vigor rootstock, self-grafted and non-grafted above 150 g, tend to have a cylindrical shape; however, fruits in the resistance rootstock tend to be flattened. The use of a vigor rootstock increased the yield of cv. Libertador, regarding the rootstock with resistance characteristics and controls, self-grafted, and non-grafted plants.